Safety and feasibility of liver resection with continued antiplatelet therapy using aspirin. (5th June 2017) - Monden, Kazuteru; Sadamori, Hiroshi; Hioki, Masayoshi; Ohno, Satoshi; Saneto, Hiromi; Ueki, Toru; Yabushita, Kazuhisa; Ono, Kazumi; Sakaguchi, Kousaku; Takakura, Norihisa
Abstract: Background: Aspirin is widely used for the secondary prevention of ischemic stroke and cardiovascular disease. Perioperative aspirin may decrease thrombotic morbidity, but may also increase hemorrhagic morbidity. In particular, liver resection carries risks of bleeding, leading to higher risks of hemorrhagic morbidity. Our institution has continued aspirin therapy perioperatively in patients undergoing liver resection. This study examined the safety and feasibility of liver resection while continuing aspirin. Methods: We retrospectively evaluated 378 patients who underwent liver resection between January 2010 and January 2016. Patients were grouped according to preoperative aspirin prescription: patients with aspirin therapy (aspirin users, n = 31); and patients without use of aspirin (aspirin non‐users, n = 347). Results: Aspirin users were significantly older ( P < 0.001), with a higher proportion of males ( P < 0.001) and higher frequencies of hypertension ( P  = 0.004) and diabetes mellitus ( P < 0.001). No significant differences were observed in intraoperative parameters. Although the frequency of major morbidity tended to be higher among aspirin users than among aspirin non‐users, no significant difference was identified. No postoperative hemorrhage was seen among aspirin users. Conclusions: Liver resection can be safely performed while continuing aspirin therapy without increasing hemorrhagic morbidity. Our results suggest that interruption of aspirin therapy is unnecessary for patients undergoing liver resection. Highlight: Monden and colleagues retrospectively assessed the safety and feasibility of liver resection while continuing aspirin treatment. They found that liver resection can be safely performed while continuing aspirin therapy perioperatively without affecting intraoperative parameters of liver resection or increasing hemorrhagic morbidity, suggesting that interruption of aspirin therapy is unnecessary.